Analysis of The Influence of Product Price and Service Quality on Consumer Loyalty at Coffee Harbor Shop Kemayoran Using Electronic Word of Mouth as A Moderating Variable - Lukyiana, Lukyiana; Nurudin, Albert (Publikasi Indonesia, 2023)
This study aims to analyze (1) the effect of product prices on Harbor Coffee Consumer Loyalty. (2) the influence of Service Quality on Coffee Harbor Consumer Loyalty. (3) the effect of product prices on consumer loyalty with electronic word of mouth as a moderating variable. (4) the influence of Service Quality on Consumer Loyalty with Electronic Word of Mouth as a moderating variable. The research population is all consumers (3) the effect of product prices on consumer loyalty with electronic word of mouth as a moderating variable with a sample of 30 respondents. Data collection techniques using questionnaires through the stages of validity and reliability testing. The data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA). This study concludes that (1) Product Prices Affect Consumer Loyalty, (2) Service Quality Affects Consumer Loyalty, (3) Product Prices and Service Quality Affect Consumer Loyalty, (4) Electronic Word of Mouth is able to moderate the effect of Product Price on Consumer Loyalty. Consumer Loyalty and (5) Electronic Word of Mouth are able to moderate the influence of Service Quality on Consumer Loyalty.